Assessing the impact of the built environment on healthy aging: A gender-oriented Hong Kong study - Chen, Shuangzhou; Bao, Zhikang; Lou, Vivian (Environmental impact assessment review, 2022)
The built environment is widely perceived as crucial in promoting the public health of older adults. Consequently, recent years have seen substantial efforts to explore linear relationships of the built environment on functional ability, a widely adopted indicator for public health of older adults. However, relevant studies highlighting the non-linear relationships and gender differences of older adults are lacking, posing potential challenges to governments for policymaking of building a sustainable and age-friendly society. Thus, this study aims to investigate non-linear relationships between the built environment (distance to transit, design, destination accessibility, density, and diversity) and functional ability of older adults by employing an ecological model of aging for a sample size of 1112 participants aged 60 and above in a typical aging Chinese society of Hong Kong with a specific emphasis on gender differences. Results reveal that non-linear relationships between the built environment and functional ability of older adults generally exist in both gender groups. However, gender differences are also distinctively found regarding the effects of the built environment on the functional ability of older adults. Males' functional ability has been improved with services (≤ 30), road lengths (≥ 6 km), bus stop (≤ 50), population density (≤ 23,000 person/km2), diverse land-use entropy index (≥ 0.4), shorter distances to the nearest hospital (≤ 1.2 km), and a closer MTR station (≤ 500 m). In comparison, females' functional ability has been improved with specific ranges of road lengths (≤ 4 or ≥ 6 km), services (≤ 30), greenery exposure (0.05 to 0.2 or ≥ 0.25), and distances to the nearest MTR (≤ 800 m). This study provides a valuable reference for various governments to implement targeted gender-based urban planning to facilitate healthy aging. •The built environment is critical for public health of older adults.•Non-linear relationships exist between the built environment and healthy aging.•Gender differences exist in the impact of the built environment on healthy aging.•The study provides a useful reference to implement gender-oriented urban planning.